Pengaruh Lingkungan dan Motivasi Kerja Terhadap Kinerja Guru di MTs Muslim Cendikia Bengkulu Tengah - Kholid Jamaluddin (UIN Fatmawati Sukarno Bengkulu, 2021)
This research aims to assess the impact of the work environment and work motivation on teacher performance at MTS Muslim Cendikia, Central Bengkulu. The specific objectives of study are: 1) to measure the influence of the work environment on teacher perfprmance, 2) to evaluate the effect of work motivation on teacher performance, and 3) to analyze the combined impact of the work environment and work motivation on teacher performance. This is a field study in wich the researcher was directly involved in data collection from the population of teachers at MTS Muslim Cendekia, Central Bengkulu. The sampling technique employed was a census sample, meaning the entire population was utilized as the sample for the research. The result of the study indicate that: 1) the work environment significantly influences teacher performance, 2) work motivation has a significant impact on teacher performance, and 3) both the work environment and work motivation, when considered together, have a significant effect on teacher performance. The implication of this research highlight the necessity tho enhace teacher performance by improving both teacher motivation and the work environment, as both factors jointly exert considerable influence.Keyword: Work Environment, Work Motivation, Teacher Performance.